Joint tagging assisted fluctuation nanoscopy enables fast high‐density super‐resolution imaging. Issue 9 (19th June 2018) - Zeng, Zhiping; Ma, Jing; Xi, Peng; Xu, Canhua
Abstract : In fluctuation‐based optical nanoscopy, investigating high‐density labeled subcellular structures with high fidelity has been a significant challenge. In this study, based on super‐resolution radial fluctuation (SRRF) microscopy, the joint tagging (JT) strategy is employed to enable fast high‐density nanoscopic imaging and tracking. In fixed cell experiment, multiple types of quantum dots with distinguishable fluorescence spectra are jointly tagged to subcellular microtubules. In each spectral channel, the decrease in labeling density guarantees the high‐fidelity super‐resolution reconstruction using SRRF microscopy. Subsequently, the combination of all spectral channels achieves high‐density super‐resolution imaging of subcellular microtubules with a resolution of 62 nm using JT assisted SRRF technique. In the live‐cell experiment, 3‐channel JT is utilized to track the dynamic motions of high‐density toxin‐induced lipid clusters for 1 minute, achieving the simultaneous tracking of many individual toxin‐induced lipid clusters spatially distributed significantly below the optical diffraction limit in living cells. Abstract : The joint tagging (JT) strategy was employed for assisting fluctuation nanoscopy to enable fast high‐density super‐resolution imaging. In this study, the JT assisted super‐resolution radial fluctuation (JT‐SRRF) microscopy obtained high‐density super‐resolution images of multicolor‐labeled subcellular microtubules with high fidelity. Furthermore, JT‐SRRF achieved the simultaneous tracking of massive individual toxin‐induced lipid clusters spatially distributed significantly below the optical diffraction limit in living cells.